LiFePO4 / AC Composite Cathodes − Long Term Cycle Life Study and Capacity Sharing Analysis. (7th July 2017) - Shellikeri, Annadanesh; Yturriaga, Steven; Zheng, Jun-Sheng; Cao, Wanjun; Read, Jeffrey A.; Jow, T Richard; Zheng, Jim P.
Abstract : Energy storage devices combining the advantages of battery and supercapacitor are of prime interest. Recently, composite cathodes combining battery materials with capacitor material have shown promise in enhancing capacity and cycle life. Lithium ion capacitor (LIC), with unique charge storage mechanism (battery anode with capacitor cathode), has the potential to synergistically incorporate composite cathode to enhance capacity and cycle life. We report here an internal hybrid LIC consisting of lithium iron phosphate / activated carbon composite cathode in combination with hard carbon anode, by integrating cycle life and capacity enhancing strategies of dry method of electrode fabrication, anode pre- lithiation and a designed anode to cathode capacity ratio, while elaborating on the faradaic / non-faradaic capacity sharing. An excellent cell capacity retention of 91% (5000 cycles) and 94% (20000 cycles) were demonstrated at low and high rates, while retaining >78% and 76% of the LFP capacity in the composite cathode, respectively.